DAMPAK BANJIR TERHADAP KONDISI SOSIAL EKONOMI PETANI DI DESA BELANTI KECAMATAN SIRAH PULAU PADANG KABUPATEN OGAN KOMERING ILIR - Ghea Utami; Amruzi Minha; Elisa Wildayana; Erni Purbiyanti; Idham Alamsyah; Yulius Yulius (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2020)
This research was done in desa. the location was found fortuitously because it is one of many village rice farmers which has affection on the flood in Belanti Village Sirah Pulau Padang District there are several purposes of this research, such as (1) Analyse the farmer’s social conditions (education, attitude and behaviour, social interaction) before and after the flood happened in Belanti Village Sirah Pulau Padang District (2) Analyse the farmer’s economic condition (revenue and income) and (3) Analyse the farmer’s doings in facing the flood as a form of a reconciliation in Belanti Village Sirah Pulau Padang District. The retrieval of the research was conducted on November 2019 until completion. This research used survey methods to collecting data. The collected data has been grouped as Primary Data and Secondary data. There are several conclusions as the result in this research, such as (1) The development of farmer’s social condition could be seen in, education, attitude and behaviour, social interaction. The writer found, the development in education has been decreased. Meanwhile, in social interaction and attitude and behaviour has been increased; (2) The farmer’s economy sector has been shifted which is found that their income has decreased. The average income of farmer in 2008 was Rp18.394.023/la/year, in eleven years later, the income drastically decreased to be Rp.8.801.581/la/year, the deviation is Rp.9.592.442/la/year which means there is an absolute decreased for farmer’s income in belanti village.